Dressing dialog for success - VOGEL, CARL (My University, 1997)
This paper addresses two questions about dialog meaning what is it where does it exist Unfortunately we quickly realize that the rst question is probably illdirected as we dont have many pretheoretic intuitions about how a dialog can mean something in the way that intuitions hold about even a multiply authored text Yet partly because for example jointly authored texts often do have meaning we feel that dialog meaning also requires exploration Further we feel a strong intuition that an adequate characterization of a successful dialog is germane to dialog meaning much in the same way that characterizing truth conditions express aspects of sentence meaning However stipulating criteria for dialog success creates a new version of the second question where does success get decided Ratings of dialog success hinge on the choice of perspective from which the dialog is viewed along with that perspectivedependent determination of whether or not the interlocutors have determined that they mean dierent things with individual expressions or classify the world dierently
PUBLISHED
Keywords: Computer Science